Hidden complexity of α7 nicotinic acetylcholine receptor desensitization revealed by MD simulations and Markov state modeling - Mariia Avstrikova; Paula Milán Rodríguez; Sean M. Burke; Ryan E. Hibbs; Jean-Pierre Changeux; Marco Cecchini (Proceedings of the National Academy of Sciences, 2025)
The α7 nicotinic acetylcholine receptor is a pentameric ligand-gated ion channel that plays an important role in neuronal signaling throughout the nervous system. Its implication in neurological disorders and inflammation has spurred the development of numerous compounds that enhance channel activation. However, the therapeutic potential of these compounds has been limited by the characteristically fast desensitization of the α7 receptor. Using recent high-resolution structures from cryo-EM, and all-atom molecular dynamic simulations augmented by Markov state modeling, here we explore the mechanism of α7 receptor desensitization and its implication on allosteric modulation. The results provide a precise characterization of the desensitization gate and illuminate the mechanism of ion-pore opening/closing with an agonist bound. In addition, the simulations reveal the existence of a short-lived, open-channel intermediate between the activated and desensitized states that rationalizes the paradoxical pharmacology of the L247T mutant and may be relevant to type-II allosteric modulation. This analysis provides an interpretation of the signal transduction mechanism and its regulation in α7 receptors.